What Does It Mean to Grow Old? : Reflections from the Humanities - Gadow, Sally; Cole, Thomas R., 1949- (Book collections on Project MUSE., 1986)
In What Does It Mean to Grow Old? essayists come to grips as best they can with the phenomenon of an America that is about to become the Old Country. They have been drawn from every relevant discipline--gerontology, social medicine, politics, health, anthropology, ethics, law--and asked to speak their mind. Most of them write extremely well [and their] sharply individual voices are heard.